2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610720
|View full text |Cite
|
Sign up to set email alerts
|

Using wearable UWB radios to measure foot clearance during walking

Abstract: Foot clearance above ground is a key factor for a better understanding of the complicated relationship between falls and gait. This paper proposes a wearable system using UWB transceivers to monitor the vertical heel/toe clearance during walking. First, a pair of very small and light antennas is placed on a point approximating to the heel/toe of the foot, acting as a transmitter and receiver. Then, the reflected signal from ground is captured and propagation delay is detected using noise suppressed Modified-Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The Wang et al [26] paper, which was the only paper that tested their system outdoors, did not report any performance metrics on MFC measurement. Yongbin Qi et al [33] reported the smallest error among these papers, showed great promise in the UWB technology. However, it is worth noting that Yongbin Qi et al [33] validated their system against an ultrasound system, which is more prone to error compared to an optical motion capture system.…”
Section: Performance Complexity and Portabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The Wang et al [26] paper, which was the only paper that tested their system outdoors, did not report any performance metrics on MFC measurement. Yongbin Qi et al [33] reported the smallest error among these papers, showed great promise in the UWB technology. However, it is worth noting that Yongbin Qi et al [33] validated their system against an ultrasound system, which is more prone to error compared to an optical motion capture system.…”
Section: Performance Complexity and Portabilitymentioning
confidence: 99%
“…Yongbin Qi et al [33] reported the smallest error among these papers, showed great promise in the UWB technology. However, it is worth noting that Yongbin Qi et al [33] validated their system against an ultrasound system, which is more prone to error compared to an optical motion capture system. Zhang et al [25] have struck a good balance between portability, performance, and complexity.…”
Section: Performance Complexity and Portabilitymentioning
confidence: 99%
See 1 more Smart Citation